Self-Compacting Concrete Using Industrial Waste Red Sand (Bauxite Residue) As Fine Aggregate (International Journal of Innovative Research in Computer Science & Technology, 2022)
Self-compacted concrete (SCC) is cast  within the formwork without compaction and it fulfills the  formwork because of its personal weight. SCC is taken into  consideration to have many benefits in contrast with  traditional concrete like improved construction, economic  and time saving, quicker construction activity etc. SCC is  produced with the same materials of ordinary concrete.  Cementatious materials are adopted to replace the cement  content in SCC so that waste materials (bauxite) from  industries and agricultural products can be used. Further  improvement in the performance of SCC is done by using  different types of fibers to produce fiber reinforced SCC and  to diffuse the crack propagation which improves mechanical  properties. The foremost goal of this paper is to collect the  literature to recognize the use of cement alternative materials  (bauxite) and fibers for reducing the environmental hazards.  This paper discusses the environmental implications due to  the technology of diverse solid wastes, and highlights their  recycling potentials and viable use for generating productive  materials.
Keywords: SCC; Compaction; Bauxite; Fiber Reinforcement; Environmental implications; recycling